El impacto de la pandemia del COVID-19 en las clases de Educación Física portuguesas (The COVID-19 pandemic impact on the Portuguese Physical Education classes) - Mendes, Pedro Cabral; Fachada, Miguel; Melo, Ricardo; Campos, Francisco; Nobre, Paulo; M. Machado-Rodrigues, Aristides (Retos, 2023)
Las restricciones inducidas por la Covid-19 condicionaron, de manera muy significativa, la vida escolar de millones de niños y jóvenes. Sin embargo, se sabe poco sobre el impacto de la pandemia en las clases de Educación Física (EF) en Portugal. El objetivo del presente estudio es describir la percepción de alumnos de Primaria Superior y Secundaria Obligatoria sobre el impacto de la pandemia en las clases de EF en Portugal. Participaron un total de 1419 alumnos de la región Centro (53,3/46,7% chicas/os, edad media 14,4 años), que respondieron presencialmente a un cuestionario anónimo. Los resultados indican que las medidas restrictivas impuestas a las clases de EF en el primer trimestre de 2020/21 acabaron teniendo un fuerte impacto en la programación de contenidos curriculares. La condición física asumió un papel importante en las clases de EF. Los participantes consideraron la escuela un espacio seguro que les protegió de posibles riesgos de contagio; expresaron una mayor satisfacción con las clases presenciales. Los niveles de satisfacción con la EF se mantuvieron el línea con los de estudios anteriores. Palabras clave: Covid-19; Educación Física; Escuela Secundaria. Abstract. The restrictions “imposed” to avoid the spread of Covid-19 disease have strongly conditioned the school life of millions of children and youth. However, little is known about the impact of the pandemic on PE classes in Portugal. The purpose of the present study is to describe the perception of secondary and high school students about the impact of the pandemic on PE classes, after the first wave of the COVID-19 outbreak. The sample comprised 1419 students aged from 12 to 16 years from the Portuguese Midlands (53% females, mean age 14,4 years-old); participants responded in person to an anonymous and self-report questionnaire. The results revealed that restrictive measures imposed on PE classes at the end of 2020 had a strong influence on selection of PE curricular contents. Physical condition of students has assumed a major role in PE enrolment. It should be also highlighted that participants revealed the school as a safe space to avoid the risks of SARS-CoV2 contagion. The surveyed students expressed greater satisfaction with the face-to-face than virtual PE classes. It should be noted that the pandemic context did not change the appreciation attributed to this subject by students. Keywords: Covid-19; Physical Education; Secondary School.